Marine Polysaccharides for Wound Dressings Application: An Overview - Shenghai Shen; Xiaowen Chen; Zhewen Shen; Hao Chen (MDPI AG, 2021)
Wound dressings have become a crucial treatment for wound healing due to their convenience, low cost, and prolonged wound management. As cutting-edge biomaterials, marine polysaccharides are divided from most marine organisms. It possesses various bioactivities, which allowing them to be processed into various forms of wound dressings. Therefore, a comprehensive understanding of the application of marine polysaccharides in wound dressings is particularly important for the studies of wound therapy. In this review, we first introduce the wound healing process and describe the characteristics of modern commonly used dressings. Then, the properties of various marine polysaccharides and their application in wound dressing development are outlined. Finally, strategies for developing and enhancing marine polysaccharide wound dressings are described, and an outlook of these dressings is given. The diverse bioactivities of marine polysaccharides including antibacterial, anti-inflammatory, haemostatic properties, etc., providing excellent wound management and accelerate wound healing. Meanwhile, these biomaterials have higher biocompatibility and biodegradability compared to synthetic ones. On the other hand, marine polysaccharides can be combined with copolymers and active substances to prepare various forms of dressings. Among them, emerging types of dressings such as nanofibers, smart hydrogels and injectable hydrogels are at the research frontier of their development. Therefore, marine polysaccharides are essential materials in wound dressings fabrication and have a promising future.